Penggunaan Kitab Kuning sebagai Sumber Belajar Fikih di MTs Al-Washliyah Insanul Kamil - Muhammad Iqbal Hafiz; Khairunnisa; Rizki Nazlia (TABYIN: JURNAL PENDIDIKAN ISLAM, 2022)
The usage of the Kitab Kuning as a fiqh resource at MTs Al-Washliyah Insanul Kamil is covered in this article's abstract. This article's discussion is on the application of instructional strategies, learning assessment, and the advantages of studying Fiqh from the yellow book. This essay was written using a case study approach along with qualitative research methodology. The location of this study is MTs Al-Washliyah Insanul Kamil. In this study, documentation, interviews, and observation are the methods used to collect data. The study's findings demonstrate that MTs Al-Washliyah Insanul Kamil instructs students in Fiqh using the wetonan approach when teaching the yellow book. A summary.Teachers utilize formative, summative, and practical assessments to gauge students' knowledge, comprehension, and skill levels in relation to learning outcomes. Finally, research findings indicate that using the yellow book to learn Fiqh has numerous advantages. For example, students can acquire indepth knowledge about worship since it is derived directly from the Arabic text, which helps them avoid understanding errors. Additionally, learning about Arabic grammar is provided, and it serves as a link to previous teachers' sanad.